Automating implant reconstruction in interstitial brachytherapy of the breast: A hybrid approach combining electromagnetic tracking and image segmentation. (November 2022) - Dürrbeck, Christopher; Sauer, Birte Christina; Lotter, Michael; Kreppner, Stephan; Strnad, Vratislav; Fietkau, Rainer; Bert, Christoph
Highlights: Assessing catheter implants using an afterloader prototype with EMT functionality. Refining EMT implant reconstruction with image processing operations. 64 patients comprising more than 1100 catheters included in the study. Excellent accuracy compared to clinical reconstruction (median deviation 0.25 mm). Streamlining implant reconstruction in interstitial brachytherapy of the breast. Abstract: Background and purpose: To develop a method for automatic reconstruction of catheter implants in interstitial brachytherapy (iBT) of the breast by means of electromagnetic tracking (EMT) with the goal of making treatment planning as time-effective and accurate as possible. Materials and methods: The implant geometry of 64 patients was recorded using an afterloader prototype with EMT functionality immediately after the planning CT. EMT data were transferred to the CT image space by rigidly registering the catheter fixation buttons as landmarks. To further improve reconstruction accuracy, the EMT reconstruction points were used as starting points to define small regions of interest (ROI) in the CT image. Within these ROIs, the catheter track was segmented in the CT using image processing operations such as thresholding and blob detection, thus refining the reconstruction. The perpendicular distance between the refined EMT implant reconstruction points and the manually reconstructed catheters by an experienced treatment planner was calculated as a measure of their geometric agreement. Results: Geometrically, the refined EMT based implant reconstruction shows excellent agreement with the manual reconstruction. The median distance across all patients is 0.25 mm and the 95th percentile is 1 mm. Refinement takes approximately 0.5 s per reconstruction point and typically does not exceed 3 min per implant at no user interaction. Conclusion: The refined EMT based implant reconstruction proved to be extremely accurate and fast compared to manual reconstruction. The presented procedure can in principle be easily transferred to clinical routine and therefore has enormous potential to provide significant time savings in iBT treatment planning whilst improving reconstruction accuracy.